Survival and compatibility of tomato grafted on solanaceous plants and by different grafting methods - Zeist, André Ricardo; de Resende, Juliano Tadeu Vilela; da Silva, Israel Felipe Lustosa; Zanin, Daniel Suek; Faria, Cacilda Marcia Duarte Rios; Giacobbo, Clevison Luiz (Científica, 2017)
The objective of this work was to evaluate plant survival and grafting compatibility in tomatoes grafted on different solanaceous plants and by different grafting methods. Nine rootstocks were evaluated: 1- minitomato accession 0224-53; 2- minitomato accession RVTC 57; 3- minitomato accession RVTC 20; 4- minitomato accession 6889-50; 5 - wild tomato species Solanum habrochaites var. Hirsutum (PI-127826); 6- wild tomato species Solanum pennellii ’LA716’; 7- cubiu (Solanum sessiliflorum); 8- physalis (Physalis peruviana); and 9- tomato cultivar Santa Cruz Kada® (control), and two grafting methods [1- full cleft grafting (FCG); and 2- approach grafting (AG)]. Throughout the crop cycle, we evaluated: plant survival rate (PSR); and grafting incompatibility (GI). By means of the results obtained, it was possible to infer that the use of wild tomato species Solanum pennellii ’LA716’ and physalis as rootstocks should not be recommended. Wild tomato species Solanum habrochaites var. hirsutum, cubiu and minitomato accessions 0224-53, RVTC 57, RVTC 20 and 6889-50 show potential for use as rootstocks. For using cubiu as rootstock, the full cleft grafting method is recommended, while for the other rootstocks, both the approach grafting method and the full cleft grafting method are feasible.